![(-2)^{2}](https://tex.z-dn.net/?f=%20%28-2%29%5E%7B2%7D%20)
is 4.
Then, 7(-2) is -14.
Then, 4 - (-14) is (-18).
Finnaly, (-18) - 8 is
[-26]
Answer:
y=-3x-14
Step-by-step explanation:
y=mx +c
m= 1/3
perp m= -3
goes through point (6,-4)
sub numbers
Answer:
It will take 3 hours. They will both have completed 11 rows.
Step-by-step explanation:
1 row of carrots per hour = frank
3 rows of tomatoes per hour = frank's mom
right now, this is how many they have completed
frank - 8 rows
mom - 2 rows
1st hour
f - 9
m - 5
2nd hour
f - 10
m - 8
3rd hour
f - 11
m - 11
Answer:
x = 2
Step-by-step explanation:
Answer:
![\huge\boxed{ \red{ \boxed{ \tt{ \frac{ {y}^{2} }{ {10}^{2} } - \frac{ {x}^{2} }{ {12}^{2} } = 1}}}}](https://tex.z-dn.net/?f=%20%20%5Chuge%5Cboxed%7B%20%20%5Cred%7B%20%5Cboxed%7B%20%5Ctt%7B%20%5Cfrac%7B%20%7By%7D%5E%7B2%7D%20%7D%7B%20%7B10%7D%5E%7B2%7D%20%7D%20%20-%20%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20%7D%7B%20%7B12%7D%5E%7B2%7D%20%7D%20%20%3D%201%7D%7D%7D%7D)
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about:</h3>
<h3>tips and formulas:</h3>
![\sf hyperbola \:equation : \\ \sf \frac{ {x}^{2} }{ {a}^{2} } - \frac{ {y}^{2} }{ {b}^{2} } = 1](https://tex.z-dn.net/?f=%20%5Csf%20hyperbola%20%5C%3Aequation%20%3A%20%20%5C%5C%20%20%5Csf%20%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20%7D%7B%20%7Ba%7D%5E%7B2%7D%20%7D%20%20%20-%20%20%5Cfrac%7B%20%7By%7D%5E%7B2%7D%20%7D%7B%20%7Bb%7D%5E%7B2%7D%20%7D%20%20%3D%201)
- vertices of hyperbola:(±a,0) and (0,±b) if reversed
![\sf \: asymptotes : \\ y = \pm\frac{b}{a} x](https://tex.z-dn.net/?f=%20%5Csf%20%5C%3A%20asymptotes%20%3A%20%20%5C%5C%20y%20%3D%20%20%20%5Cpm%5Cfrac%7Bb%7D%7Ba%7D%20x)
<h3>given:</h3>
- vertices: (0,±10)
- the hyperbola equation is inversed since the vertices is (0,±10)
- asymptotes:
![\pm \frac{5}{6}x](https://tex.z-dn.net/?f=%5Cpm%20%5Cfrac%7B5%7D%7B6%7Dx)
<h3>let's solve:</h3>
- the asymptotes are in simplest and we know b is ±10
according to the question
![y = \sf \frac{5 \times 2}{6 \times 2} x \\ y = \frac{10}{12} x](https://tex.z-dn.net/?f=y%20%3D%20%20%5Csf%20%20%5Cfrac%7B5%20%5Ctimes%202%7D%7B6%20%5Ctimes%202%7D%20x%20%5C%5C%20y%20%3D%20%20%5Cfrac%7B10%7D%7B12%7D%20x)
therefore we got
note: the equation will be inversed
let's create the equation:
![\sf substitute \: the \: value \: of \: a \: and \: b : \\ \sf \frac{ {y}^{2} }{ {10}^{2} } - \frac{ {x}^{2} }{ {12}^{2} } = 1](https://tex.z-dn.net/?f=%20%5Csf%20substitute%20%5C%3A%20the%20%5C%3A%20value%20%5C%3A%20of%20%5C%3A%20a%20%5C%3A%20and%20%5C%3A%20b%20%3A%20%20%5C%5C%20%20%5Csf%20%20%5Cfrac%7B%20%7By%7D%5E%7B2%7D%20%7D%7B%20%7B10%7D%5E%7B2%7D%20%7D%20%20-%20%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20%7D%7B%20%7B12%7D%5E%7B2%7D%20%7D%20%20%3D%201)